Botulinum Toxin: An Innovative Approach to Treating Acne and Acne Scars: A systematic review - Podraza, Anna; Sacher, Karolina; Maciaszek, Oliwia; Turemka, Mariola; Chmiel, Marianna (Journal of Education, Health and Sport, 2025)
Introduction and Objective: Acne is one of the most common dermatological diseases. It mainly affects young people, but is more and more common in older people. There are reports on the effectiveness of treatment with botulinum toxin in acne vulgaris, acne rosacea and in the treatment of acne scars. The article takes into account research examining the effect of BTX as a method of treating acne. The results indicate that the use of BTX therapy as the method of treating acne may be effective. However, further research on its use in this therapy is necessary. Methods: The article is a review on the effect of botulinum toxin on acne vulgaris, rosacea and on the treatment of scars. works from 1999-2024 were used to create the article. On their basis, conclusions were drawn. Results: The results obtained based on the research review indicate a great potential for the use of botulinum toxin in the treatment of acne and acne scars. However, more research is needed on a larger population of patients to clearly assess the effectiveness of botulinum toxin therapy and adjust the appropriate doses of the preparation.